Economic development social structure and population growth - "D'Souza , Victor S." (New Delhi, 1985)
This unique and path-breaking book establishes, contrary to widely held belief, that in rural areas the size of the family is not influenced by economic levels or status differences, but by the opportunities of inter-generational mobility.
Keywords: India economic conditions 1947